LEGALITAS SURAT KUASA ISTIMEWA DALAM PENGUCAPAN IKRAR TALAK DI PENGADILAN AGAMA DI INDONESIA - Holid, Muhammad; Manab, Abd.; Karimah, Alifatul (Program Studi Hukum Keluarga Islam, 2022)
Proceedings in the Religious Courts can be carried out directly or indirectly. Directly, it means that the litigants come to the court themselves to take care of their interests until they are finished. If the proceedings are indirect, then the litigating party can represent the case to the recipient of the power of attorney. The method taken is to make a special power of attorney in which the power of attorney authorizes the recipient of the power of attorney to take legal action regarding the case faced by the power of attorney. A special power of attorney can be in the form of an authentic deed or a private deed. The power of attorney can take various legal actions to represent the interests of the attorney in the case at hand in accordance with the special power of attorney that has been made. Special Power of Attorney is a power of attorney made to carry out certain very important legal actions which can only be carried out by the power of attorney himself and may not be authorized to another person even though using a special power of attorney. Based on Article 123 of HIR that a special power of attorney can only be given in the form of a valid letter. R. Soesilo interpreted it in the form of an authentic deed (notary deed). In addition, for those who think that a special power of attorney must be in the form of an authentic deed, in practice there are still differences of opinion as to whether it must be made before a notary or can be made before another official. As the example of practice in the Religious Courts that I described above, there are those who argue that a special power of attorney that will be used to carry out legal actions before a trial can be made enough before the clerk of the Court. Based on the explanation above, the writer is interested in formulating the problem as follows: How is the legality of a special power of attorney in pronouncing the divorce pledge? and How is the legality of the legalization and waarmeking of a power of attorney under the hand in pronouncing the divorce pledge?